ESTIMASI INFLASI DI INDONESIA DENGAN MENGGUNAKAN METODOLOGI BOX JENKINS - Bunyamin ,; Nevi Danila (Universitas Trisakti, 2011)
The objective of this paper is to predict Indonesia's inflation rate in 2009 by employing BOX-JENKINS (ARIMA) model. The prediction of inflation rate is very important since the inflation affects us in economy aspect. Moreover, by knowing the approximate inflation in the future will help companies to plan the operational cost better. It also will help the government to anticipate the predicted inflation by making good policies, thus the prosperity of Indonesia people will be achieved. AR (2) is the best ARIMA model that we obtain. By employing AR (2), we predict the inflation rate in 2009 is 10.48%. This number is not surprising since inflation rate in Indonesia is mainly affected by exchange rate. As we know that the global crisis will start recovering in early 2010 (Yearly Bank Indonesia Report, 2008). The impact is that exchange rate pressure will be still high in 2009, it is due to non-optimal export and limited foreign fund's inflow.